IMPLEMENTASI KEBIJAKAN KABUPATEN LAYAK ANAK DALAM PERLINDUNGAN KHUSUS DI KABUPATEN MOJOKERTO - Wiwin Windari (Halu Oleo University, 2025)
This study aims to describe the Implementation of the Child-Friendly Regency Policy in special protection in Mojokerto Regency. The method used in this study is a qualitative research approach, employing data collection techniques that include observation, interviews, and documentation. The results of this study explain that the implementation of the Decent Regency Policy in Special Protection in Mojokerto Regency has been running well. This is shown by the implementation of efforts to handle children who need special protection, such as children in emergencies, special protection is provided through psychosocial support and basic needs assistance; protection of children who conflict with the law is carried out through psychological and legal aid; and protection for child victims of violence is provided through socialization, facilitating online complaint services and assistance according to the level of the case.